2014
DOI: 10.11646/zootaxa.3882.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Family-group names of Recent fishes

Abstract: The family-group names of animals (superfamily, family, subfamily, supertribe, tribe and subtribe) are regulated by the International Code of Zoological Nomenclature. Family names are particularly important because they are among the most widely used of all technical animal names. Apart from using the correct family-group name according to the Code, it is also important to use one unique universal name (with a fixed spelling) to avoid confusion. We have compiled a list of family-group names for Recent fishes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
100
2
11

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 218 publications
(130 citation statements)
references
References 369 publications
0
100
2
11
Order By: Relevance
“…The material was then counted and identified to the lowest possible level using revisionary studies by Bertaco & Malabarba (2007) Queiroz et al (2013), Reis et al (2005), and comparisons with identified material deposited in the fish collections whenever needed. The classification adopted follows Reis et al (2003), Wiley & Jonson (2010), and Van Der Laan et al (2014), with genera listed in alphabetical order within each family. Voucher specimens were deposited in the fish collections of the Museu de Zoologia da Universidade de São Paulo (MZUSP) and the Universidade Federal de Rondônia, Ictiologia (UFRO-I).…”
Section: Samplingmentioning
confidence: 99%
“…The material was then counted and identified to the lowest possible level using revisionary studies by Bertaco & Malabarba (2007) Queiroz et al (2013), Reis et al (2005), and comparisons with identified material deposited in the fish collections whenever needed. The classification adopted follows Reis et al (2003), Wiley & Jonson (2010), and Van Der Laan et al (2014), with genera listed in alphabetical order within each family. Voucher specimens were deposited in the fish collections of the Museu de Zoologia da Universidade de São Paulo (MZUSP) and the Universidade Federal de Rondônia, Ictiologia (UFRO-I).…”
Section: Samplingmentioning
confidence: 99%
“…The family classification followed Van der Laan et al (2014), while genus and species classification followed Eschmeyer et al (2017 Table 1. Body slender, laterally compressed, deepest at beginning of first dorsal fin.…”
Section: Methodsmentioning
confidence: 99%
“…Publications of all authors referenced by Billberg were examined for verification of the sources of the scientific names that hes uses, and all names also cross-checked with the Catalog of Fishes (Eschmeyer & Fricke, 2015), and van der Laan et al (2014). Relative validity of taxa follows Eschmeyer & Fricke (2015) unless otherwise stated.…”
Section: Methodsmentioning
confidence: 99%